方程|x^2-2=lg(x+√2+1)|的实根的个数是
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 11:01:08
方程|x^2-2=lg(x+√2+1)|的实根的个数是方程|x^2-2=lg(x+√2+1)|的实根的个数是方程|x^2-2=lg(x+√2+1)|的实根的个数是是两个
方程|x^2-2=lg(x+√2+1)|的实根的个数是
方程|x^2-2=lg(x+√2+1)|的实根的个数是
方程|x^2-2=lg(x+√2+1)|的实根的个数是
是两个
解方程:lg(x-1)+lg(x+2)=1
解方程:lg(x+1)+lg(x-2)=lg4
解方程lg(x+1)+lg(x-2)=lg4?
求解方程lg(x+3)+lg(x-1)=lg(x^2-2x-3).
lg(x-1)+lg(x-2)=lg(x+2) 解方程 .
对数函数方程~lg(12-5x)-lg(3+2x)=lg(4-3x)-lg(2x+1)
解方程lg(x^2+x)=lg(x+1)?等于1?
2lg^2 x - (1/2) lg x^2 -1=0 解方程
解对数方程 lg(2x-1)^2-lg(x-3)^2=2
lg^2(x-1)-lg(x-1)^2-3=0 解方程
lg(2x+2)+lg(15-x)=1+lg3解方程
lg(x^2+1)-lg(x-2)=1 x^2+1=10x-20 解方程,求x
lg(x﹢1)﹢lg(x‐2)=lg4解方程
lg(2-2x)-lg(x+1)
lg(2-x)-lg(x-1)>0
lg(x²-2x-3)=lg(6+x-x²)解方程
方程lg(4^x+2)=lg2^x+lg3^x
若lg(x-1)+lg(3-x)=lg(2-x),则x=